Economic Spatial Patterns and Human Development Index Districts and Cities in Five Southern Sumatera Provinces - Ahmad Dhea Pratama; Ukhti Ciptawaty (Jurnal Pembangunan Wilayah dan Kota, 2022)
The Spatial linkages between regions are an important part of a regional economy as an analysis of relations and interactions between regions. Regional economic studies tend to focus only on the independence of a region so that it does not consider the spatial effects that occur between one region and another. This study focuses on looking at spatial autocorrelation which will produce spatial patterns and spatial linkages between regions of the gross regional domestic product and the human development index, with the findings of seeing spatial interactions and patterns of similarities or differences in the formation of the two variables between regions. The research area focuses on 60 districts and cities in 5 provinces of Southern Sumatera with the 2015-2019 research year, the analysis method uses Geographic Information Systems with Geoda software, the results of the calculations will produce Moran’s I, LISA Significance and Clustered maps.  The outcomes show that there has been a spatial relationship as certain autocorrelation of GRDP and HDI, the formation of the economy and human capital has a spatial relationship, results of Moran'I show that the positive value of the two variables has a group pattern and has a level of formation of GRDP and HDI with the same characteristics, moran scatterplot shows the similarity with the resulting region divided into 4 quadrants. The LISA cluster map and the LISA marking are the similarities in the findings of the GRDP and HDI results, but both variables have no findings of Low-high patterns.